Pengaruh Profitabilitas, Pertumbuhan Aset, Dan Likuiditas Terhadap Harga Saham Syariah Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index Periode 2012-2014 - Sakinah, Sakinah; , Eni Setyowati, SE, MSi; , Dr. Imron Rosyadi, M.Ag (2016)
Sharia stocks in Jakarta Islamic Index (JII) are corporations stocks while are in operation not contradiction with Islamic Sharia, the object of this research is all of sharia stocks who was listed in Jakarta Islamic Index (JII) that are listed at the official site of the Bursa Efek Indonesia (BEI) that is www.idx.co.id . This research was a purpose to provide empirical evident about profitability, growth of asset, and liquidity influence towards to stock prices of sharia. The variables used are profitability, growth of asset, and liquidity as independent variables and stock prices of sharia as dependent variable. The object of this research is 30 of sharia stocks who was listed in Jakarta Islamic Index (JII) that are listed at the official site of the Bursa Efek Indonesia (BEI) period 2012-2014. The type of the data is secondary data, the statistic method used to test on the research hypothesis is regression/OLS (Ordinary Least Square). The result shows that profitability, growth of asset, and liquidity are significant and positive influence to stock prices of sharia. This shows that there are the links between dependent variable and independent variable.